The product of a weighted composition operator W_(f,Ï†)^* with the adjoint of a weighted composition operatorã€– Wã€—_(f,Ïˆ)^* on the Hardy space H^2 - Hussien Mohammed, Alaa; H. Abood, Eiman (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper we study the product of a weighted composition operator with the adjoint of a weighted composition operator on the Hardy space . We will try to completely describe when the operator is invertible , isometric and unitary .